Photoemission Spectroscopic Evidence of Multiple Dirac Cones in Superconducting BaSn3Supported by the National Key R&D Program of China (Grant No. 2016YFA0300204), the National Natural Science Foundation of China (Grant Nos. U2032208 and 11874264), and the Natural Science Foundation of Shanghai (Grant No. 14ZR1447600). Y. F. Guo acknowledges the starting grant of ShanghaiTech University and the Program for Professor of Special Appointment (Shanghai Eastern Scholar). Part of this research used Beamline 03U of the Shanghai Synchrotron Radiation Facility, which is supported by ME2 project (Grant No. 11227902) from the National Natural Science Foundation of China. ZJW was supported by the National Natural Science Foundation of China (Grant No. 11974395), the Strategic Priority Research Program of Chinese Academy of Sciences (Grant No. XDB33000000), and the Center for Materials Genome. The authors also thank the support from Analytical Instrumentation Center, SPST, ShanghaiTech University (Grant No. SPST-AIC10112914). (November 2021) - Huang 黄, Zhe 喆; Shi 石, Xianbiao 贤彪; Zhang 张, Gaoning 高宁; Liu 刘, Zhengtai 正太; Cho, Soohyun; Jiang 江, Zhicheng 志诚; Liu 刘, Zhonghao 中灏; Liu 刘, Jishan 吉山; Yang 杨, Yichen 逸尘; Xia 夏, Wei 威; Zhao 赵, Weiwei 维巍; Guo 郭, Yanfeng 艳峰; et al.
Abstract : Signatures of topological superconductivity (TSC) in superconducting materials with topological nontrivial states prompt intensive researches recently. Utilizing high-resolution angle-resolved photoemission spectroscopy and first-principles calculations, we demonstrate multiple Dirac fermions and surface states in superconductor BaSn3 with a critical transition temperature of about 4.4 K. We predict and then unveil the existence of two pairs of type-I topological Dirac fermions residing on the rotational axis. Type-II Dirac fermions protected by screw axis are confirmed in the same compound. Further calculation for the spin helical texture of the observed surface states originating from the Dirac fermions gives an opportunity for realization of TSC in one single material. Hosting multiple Dirac fermions and topological surface states, the intrinsic superconductor BaSn3 is expected to be a new platform for further investigation of topological quantum materials as well as TSC.